2014
DOI: 10.1111/crj.12223
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pressure and volume‐controlled ventilation in laparoscopic cholecystectomy operations

Abstract: In this study, with volume-controlled ventilation anaesthesia in laparoscopic cholecystectomy, higher tidal volume and lower alveolar-arterial oxygen gradient were achieved after pneumoperitoneum. These findings indicated that VCV mode can provide a better alveolar ventilation than PCV mode in laparoscopic cholecystectomy operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
0
17
1
1
Order By: Relevance
“…VCV was associated with lower maximal plateau pressures, greater V T , and less dead-space ventilation. 86 In an observational study, the risk of PPC was higher in patients who received PCV compared with VCV, particularly with PEEP <5 cm H 2 O. 87 A meta-analysis regarding intraoperative ventilation mode in obese patients found VCV to be superior to PCV.…”
Section: Modes Of Mechanical Ventilationmentioning
confidence: 99%
“…VCV was associated with lower maximal plateau pressures, greater V T , and less dead-space ventilation. 86 In an observational study, the risk of PPC was higher in patients who received PCV compared with VCV, particularly with PEEP <5 cm H 2 O. 87 A meta-analysis regarding intraoperative ventilation mode in obese patients found VCV to be superior to PCV.…”
Section: Modes Of Mechanical Ventilationmentioning
confidence: 99%
“…Laparoscopic surgery has been used increasingly in many surgical procedures because of the shorter hospital stay, minimal postoperative pain and rapid recovery [1]. To obtain adequate visualization and reveal surgical area, the CO2 pneumoperitoneum method is used during the operation, but the increased intra-abdominal pressure during this type of surgery may cause problems, especially with the cardiorespiratory system [2]. Various ventilatory strategies are recommended to solve this problem and achieve better oxygenation during laparoscopy.…”
mentioning
confidence: 99%
“…Additionally, it ensures collapsed alveoli open up by extending inspiratory time using adequate positive endexpiratory pressure levels [4]. Whether PCV is superior to VCV during laparoscopic surgery is still debatable [2,3,[5][6][7][8][9][10]. In some studies, VCV provides better alveolar ventilation than PCV [2], but in other studies, PCV results in better oxygenation [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the above study by Aydın et al (1), which provided a comparison between pressurecontrolled ventilation (PCV) and volume-controlled ventilation (VCV) during laparoscopic cholecystectomy surgery on the effects of intraoperative pneumoperitoneum on haemodynamic data, respiratory parameters and arterial blood gas readings. The study found that haemodynamic variables were unchanged between the two groups but that VCV at 8-10 mL/kg resulted in higher tidal volumes (TVs) being attained and achievement of lower alveolararterial oxygen gradients than ventilation PCV.…”
mentioning
confidence: 99%